Assessment of Cell Viability in Electrically Excitable Muscle Cells Through Intact Twitch Stimulation - Bauer, Julian; Head, Stewart I.; Friedrich, Oliver (Cell Viability Assays (2nd Edt.), 2023)
Muscle cells (i.e. skeletal muscle fibers) are fully viable and functional when their excitation-contraction (EC) coupling machinery is intact. This involves intact membrane integrity with polarized membrane, functional ion channels for action potential generation and conduction, an intact electro-chemical interface at the level of the fiber’s triad, followed by sarcoplasmic reticulum Ca2+ release, and subsequent activation of the chemico-mechanical interface at the level of the contractile apparatus. The ultimate end result is then a visible twitch contraction upon a brief electrical pulse stimulation. For many biomedical studies involving single muscle cells, intact and viable myofibers are of utmost importance. Thus, a simple global screening method that involves a brief electrical stimulus applied to single muscle fibers and assessment of visible contraction would be of high value. In this chapter, we describe step-by-step protocols to (i) obtain intact single muscle fibers from freshly dissected muscle tissue using an enzymatic digestion procedure and (ii) provide a workflow for the assessment of twitch response of single fibers that can be ultimately classified as viable. For this, we have prepared a unique stimulation pen for which we provide the fabrication guide for do-it-yourself rapid prototyping to eliminate the need for expensive specialized commercial equipment.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Contraction; Electrical stimulator; Enzymatic dissociation; Single fiber; Skeletal muscle; Twitch stimulation